Fostering internationalization: an American–Danish semester‐long undergraduate nursing student exchange program. (5th March 2013) - Baernholdt, M.; Drake, E.; Maron, F.; Neymark, K.
<x xml:space="preserve">Abstract</x> Aim This paper describes the development, implementation and evaluation of a semester‐long exchange program between two Bachelor of Science in Nursing programs in the USA and Denmark. Background Nurses globally need to provide culturally sensitive care for an ethnically diverse population. Competencies on how to do so should start in basic nursing programs. A useful strategy is through immersion into another culture through an exchange program. Little is known about successful strategies for two‐way or 360° exchange programs between schools from different countries. Guided by experiential learning theory, we developed an exchange program with the objective of enhancing nursing students' cultural competence through knowledge building, attitudes and behaviour development. Lessons learned and implications for educational institutions and policy are discussed. Conclusion In internationalization of nursing education, an awareness of underlying cultural values regarding nursing competence and taking appropriate action are important for success. Other areas for a successful exchange program include matching of courses or content across schools, clear objectives and evaluation plans. Finally, flexibility and open communication are key components when setting up a 360° exchange program.